Three-Dimensional Ice-Flow Recovery from Ascending–Descending DInSAR Pairs and Surface-Parallel Flow Hypothesis: A Simplified Implementation in SNAP Software - Alejandro Téllez-Quiñones; Adán Salazar-Garibay; Beatriz I. Cruz-Sánchez; Hugo Carlos-Martínez; Juan C. Valdiviezo-Navarro; Victor Soto (Remote Sensing, 2025)
By considering two differential interferometric SAR signals, recovered from synthetic aperture radar (SAR) images, it has been possible to estimate the glacier velocity vector, from a method proposed by the authors Joughin, Kwok, and Fahnestock (JKF) in 1998. Although the JKF method normally works well under certain SAR observation conditions, we found a reformulated version of the main equation of this technique that may improve this interesting methodology. Thus, we present a mathematical review of this method, and a validation of our result in terms of accuracy, with some computer simulations. The innovation proposed is a simplified way to implement JKF’s work in the Sentinel Application Platform (SNAP) software, exemplified with some images from the Canadian Arctic. Generally, a north–east–up displacement estimation is considered, by using reference orthogonal coordinates, independent of the SAR image coordinates. However, we propose a methodology to estimate this velocity vector in terms of ascending or descending image coordinates. Given the importance of the JKF work, we believe that this investigation could contribute to the improvement of this technique, beyond the existence of other modern and independent methodologies.